Role of the Government in Promoting Dairy Sector: Evidence from Indian States (International Journal of Innovative Research in Engineering & Management, 2022)
India is the world's largest milk producer,  accounting for 22% of the world's milk supply in 2017. Five Indian states produced over 50% milk in 2016. The  Indian dairy sector also played a major role in raising the  socio-economic status of the rural landless, besides small  and medium farm households. Besides, this sector helps  reduce rural poverty by providing employment  opportunities for rural workers, particularly women.  Several factors have contributed to India's rising milk  production, including the role of co-operatives. The  present study examines the dairy industry's output and  employment performance. Data show that the dairy  industry contributes around two percent of the total  manufacturing industry output while generating around  one percent of the entire manufacturing industry  employment jobs. The studies further examine the  performance of private, public, and cooperative dairy  firms. Data confirm that the Indian co-operative sector  contributes about 30% of total revenue, with Indian private  companies and government companies/subsidiary  companies contributing 23.5% and 11%, respectively. In  contrast, foreign firms contribute around 8.6%.  Additionally, the study examines the government's role in  India's milk production while controlling for natural  disaster factors. The results show that state government  expenditure for dairy development and implementation of  dairy-related policies enhanced milk production and per  capita availability in the Indian states.
Keywords: Dairy industry; fixed effect estimate; Government policy; India; Milk production